Elimination processes for organic micropollutants in seawater : application to shellfish hatcheries - Couleaud, Julie (HAL CCSD, 2023)
The seawater (SW) used in hatcheries for mollusk cultivation is contaminated with both biological and chemical substances. This adversely affects mollusk growth and increases larval mortality. This study focuses on the chemical pollution of SW supplied to hatcheries and evaluates treatment processes. Targeted analysis has shown the recurrent presence of ketoprofen, naproxen, caffeine, metolachlor, and metolachlor-ESA. Adsorption processes in closed reactors and on activated carbon (AC) beds were investigated. The adsorption capacity decreases in the presence of marine organic matter (MOM) and depends on the characteristics of the molecules and the AC used.The transfer is affected by the presence of MOM but not by salinity. Conversely, the adsorption kinetics through an AC bed are slowed by salinity and not by MOM. The simulation of breakthrough in an industrial AC bed has been performed. Photolysis of organic micropollutants was also studied. Salinity retards photolysis, and some identified pollutants, such as ketoprofen and, generate degradation byproducts. Finally, the impact of the presence of organic micropollutants during fertilization and on the development of Pacific oyster larvae were examined. The use of UF and CAG processes has been shown to be compatible with hatchery culture. L'eau de mer (EDM) utilisée dans les écloseries pour l'élevage des mollusques contient des substances biologiques et chimiques. Certaines nuisent à la croissance des mollusques et augmentent la mortalité des larves. Cette étude porte sur la pollution chimique de l'EDM alimentant les écloseries et évalue les procédés de traitement. Une analyse ciblée a montré la présence récurrente du kétoprofène, du naproxène, de la caféine, du métolachlore, et du métolachlore-ESA. Les procédés d’adsorption en réacteur fermé et sur lit de charbon actif (CA) ont été étudiés. La capacité d'adsorption diminue avec la présence de matière organique marine (MOM) et dépend des caractéristiques des molécules et des CA utilisés. La cinétique diminue du ...